Defluoridation of Drinking Water in India - Singh, Bhoomika (The Scientific Temper, 2022)
Water supply is a daily necessity and key factor in human health and well being. The International Standards for Drinking Water (WHO, 1.9 –7.1) status that water intended for human consumption must be free from organisms and from concentrations of chemical substance that may be a hazard to health, in addition, supplies of drinking water should be as pleasant to drink as circumstance permit. Fluorosis, a slow, progressive, crippling maladyknown to be prevalent in district in 15 centers city’s areas. It caused by the intake of water contaminated with fluoride beyond the tolerable limits of 1.5 ppm. India is not the only country, but several other are severely affected by the problem of fluorosis; which includes U.S.A., Morocco, Algeria, Libya, Egypt, Jordan, Turkey, Iraq, Iran, Pakistan, Kenya, South Africa, China, Australia, New Zealand, Japan and Thailand etc. The concentration of fluoride is critical for dental health in children too high a concentration of fluoride in drinking water can result in dental and skeletal fluorosis in children, but a small amount is essential for the prevention of dental caries. The desirable concentration varies with average ambient temperatures varies with a average ambient temperature; 0.9-1.7 mg/L at 10oC, 0.7-1.2 mg/L at 20oC and 6-0.8 mg/L at 30oC, all concentrations, expressed as F. Physiological properties of fluoride have been wall documented. In higher doses it may result in the manifestation of certain abnormalities, including; motting of teeth, kidney damage and skeletal aberrations ranging from stiffness to a permanent skeletal, aberrations ranging from stiffness to permanent, crippling skeletal rigidity. Maximum ill ain and rigidity around the affected areas, restriction the movement. In several cases of fluoroseffects detected in the neck, spine, knee, pelvic, shoulder and small joints of hand and feet, producing pis, complete rigidity of joints in crippling deformity.